Distribution of Oil Palm Starch for Different Levels and Portions of Oil Palm Trunk - Nur Syuhada Omar; Edi Suhaimi Bakar; Nurulasikin Md. Jalil; Paridah Md. Tahir; Wan Md. Zin Wan Yunus (Masyarakat Peneliti Kayu Indonesia, 2011)
It is widely known that starch can be heated to have adhesive characteristic. The properties of starch rich, low density oil palm wood from the inner part of oil palm trunk (OPT) have been seen to be possible improved through steam-densification process by using in situ starch as binding agent. For that, the distribution and characteristic of the extracted starch at different height and portions of OPT are first need to be investigated. Starch extraction of OPT was made by traditional grating-dissolving method in water. Starch distributions were found more concentrated in core portion and it increased as the heights increasing. At the first 2 m height above the ground, mean extracted starch content was 2.9%, 4.3% and 5.6% for the outer, middle and core respectively. Regardless of portion, mean extracted starch content was 4.3%, 7.4%, 7.7% and 8.5% for the first, second, third, and fourth 2 m trunk height respectively. Regardless of level, mean extracted starch content was 4.9%, 7.2% and 8.8% for the outer, middle and core portion respectively. Other study using Na2S2O5 as solvent gave 7.15% mean starch content for the oil palm slabs (the outer portion). Further study on the extracted starch characterization, it was found that the starch from core portion turned into darker blue color than the outer, and the starch from upper level turned into darker blue color than the lower level when they were subjected to iodine test. The blue color is usually used to indicate the purity of starch, the darker the color, the purer the starch. The results suggest that both the extracted starch content and the starch purity were showing the same trend, increased from outer inside and from bottom upside, in the OPT.